2014
DOI: 10.1039/c4nr00983e
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanocatalysts loaded on graphene oxide-dispersed carbon nanotubes with greatly enhanced peroxidase-like catalysis and electrocatalysis activities

Abstract: A powerful enzymatic mimetic has been fabricated by employing graphene oxide (GO) nanocolloids to disperse conductive carbon supports of hydrophobic carbon nanotubes (CNTs) before and after the loading of Pt nanocatalysts. The resulting GOCNT-Pt nanocomposites could present improved aqueous dispersion stability and Pt spatial distribution. Unexpectedly, they could show greatly enhanced peroxidase-like catalysis and electrocatalysis activities in water, as evidenced in the colorimetric and electrochemical inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 47 publications
0
51
0
1
Order By: Relevance
“…[15][16][17] In our previous studies, we conrmed that the presence of multiwall carbon nanotubes (MWCNTs) could greatly enhance the catalytic activity of cobalt phthalocyanine (CoPc, an enzyme mimic catalyst) for H 2 O 2 activation because of their excellent electrical properties. [15][16][17] In our previous studies, we conrmed that the presence of multiwall carbon nanotubes (MWCNTs) could greatly enhance the catalytic activity of cobalt phthalocyanine (CoPc, an enzyme mimic catalyst) for H 2 O 2 activation because of their excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In our previous studies, we conrmed that the presence of multiwall carbon nanotubes (MWCNTs) could greatly enhance the catalytic activity of cobalt phthalocyanine (CoPc, an enzyme mimic catalyst) for H 2 O 2 activation because of their excellent electrical properties. [15][16][17] In our previous studies, we conrmed that the presence of multiwall carbon nanotubes (MWCNTs) could greatly enhance the catalytic activity of cobalt phthalocyanine (CoPc, an enzyme mimic catalyst) for H 2 O 2 activation because of their excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our experiment, PCN shows an enhanced activity than PC. Pt nanoparticles have been reported as one of typical peroxidase mimetics [11], so an obvious absorption at 652 nm of the TMB + H 2 O 2 + Pt system (curve d) is observed. When Pt and PCN were mixed mechanically as the ratio of samples, there is also an adsorption at 652 nm.…”
Section: Peroxidase-like Activity Of Pt/pcnmentioning
confidence: 90%
“…A series of inorganic nanomaterials including Au NPs [3], Fe 3 O 4 NPs [4], Co 3 O 4 NPs [5], V 2 O 5 nanowires [6], carbon dots [7], graphene oxide [8], single-walled carbon nanotubes [9] and metallic nanocomposites [10] have been found to present unexpected enzyme-like activities. As the most known one, noble metal platinum (Pt) is chemically inert at bulk scales but can serve as the important catalysts at nanoscales because of their unique size, shape and the increased specific surface area [11]. Many reports demonstrated that Pt nanoparticles can exhibit peroxidase-like catalysis activity for the detection of H 2 O 2 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…519 Interestingly, a powerful enzymatic mimetic has been fabricated by employing GO nanocolloids to disperse conductive carbon supports of hydrophobic CNTs before and after the loading of Pt nanoparticles. 520 The resulting GO@CNT-Pt nanocomposites present improved aqueous dispersion stability and Pt spatial distribution. They showed greatly enhanced peroxidase-like catalysis and electrocatalytic activities in water.…”
Section: Cnts For Enzyme Immobilizationmentioning
confidence: 99%